Kinetics of phosphorus sorption/desorption by soil aggregates in a long‐term revegetation desert ecosystem. (23rd June 2022) - Li, Chengyi; He, Mingzhu; Ren, Jianxin; Li, Manfei; Tang, Liang
Abstract: Elucidating the kinetics of phosphorus (P) sorption and desorption in soil aggregates of different sizes has important implications for the regulation of plant growth and development in revegetation desert ecosystems. In this study, the Freundlich models were used to describe the kinetics of P sorption and desorption by soil aggregates of five sizes (0.5–0.25, 0.25–0.15, 0.15–0.10, 0.10–0.05 and <0.05 mm) in a long‐term revegetation desert ecosystem. The results showed that long‐term (>65 years) revegetation significantly improved the properties of desert soil in terms of P fractions ( p < 0.05), soil bulk density ( p < 0.05), and soil type. The Freundlich models well‐described P sorption and desorption by soil aggregates in the revegetated desert. Soil aggregates of 0.25–0.15 mm adsorbed the lowest amount of P (P adsorbed: KF = 0.26, n = 0.97) but desorbed the highest amount of P (P desorbed: KF = 2.41, n = −0.97). Soil aggregates of <0.05 mm adsorbed the most P (P adsorbed: KF = 0.60, n = 0.85) but desorbed the lowest P (P desorbed: KF = 1.67, n = −1.00). Furthermore, P sorption was fastest when the added P was 0–1.0 mg L −1, and P desorption was fastest at 1–3 hr. Soil aggregates that were 0.25–0.15 mm in size had the highest mass proportion in the long‐term revegetation desert and played a key role in supporting available P for plant development. Soil aggregates of <0.05 mm adsorbed the most P; however, their contribution was constrained because they had the smallest mass proportion and the lowest amount of P desorption.